2015
DOI: 10.1142/s0219843615500127
|View full text |Cite
|
Sign up to set email alerts
|

Handing Over Objects to Human in a Friendly and Comfortable Manner

Abstract: In this paper, a robotic motion planning scheme is proposed to generate hand-over motions in a friendly and comfortable manner. Two sub-problems are studied: The determination of the¯nal target position (where the robot should hand over the object to) and the generation of humanlike motion in the hand-over process (how the robot should hand over the object to the position). First, experiments of di®erent subjects are conducted to explore the common characteristics in the optimal hand-over positions. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…After removing duplicates ( n = 3,639 removed) and after title and abstract screening ( n = 5,435 removed), the full text of 18 studies were scanned and 10 studies were found to meet our eligibility criteria [ n = 8 removed: no active handover = 4 ( Salleh et al, 2011 ; Parastegari et al, 2018 ; Kato et al, 2019 ; Neranon, 2020 ), non-relevant outcome = 2 ( Korkiakangas et al, 2014 ; Carfì et al, 2019 ), no human kinematic or force data = 2 ( Xie and Zhao, 2015 ; Chan et al, 2020 )]. Thus, we included 10 studies in our systematic review that investigated the characteristics of human-human handover actions and their influencing factors, such as the handover object weight and availability of sensory information ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates ( n = 3,639 removed) and after title and abstract screening ( n = 5,435 removed), the full text of 18 studies were scanned and 10 studies were found to meet our eligibility criteria [ n = 8 removed: no active handover = 4 ( Salleh et al, 2011 ; Parastegari et al, 2018 ; Kato et al, 2019 ; Neranon, 2020 ), non-relevant outcome = 2 ( Korkiakangas et al, 2014 ; Carfì et al, 2019 ), no human kinematic or force data = 2 ( Xie and Zhao, 2015 ; Chan et al, 2020 )]. Thus, we included 10 studies in our systematic review that investigated the characteristics of human-human handover actions and their influencing factors, such as the handover object weight and availability of sensory information ( Mason and Mackenzie, 2005 ; Becchio et al, 2008 ; Gonzalez et al, 2011 ; Meyer et al, 2013 ; Hansen et al, 2017 ; Controzzi et al, 2018 ; Bekemeier et al, 2019 ; Cini et al, 2019 ; Döhring et al, 2020 ; Sutiphotinun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The First-order Retraction RRT (FR-RRT) algorithm 30 was used by Xie and Zhao 31 to generate collision-free trajectories for a four-DOF robotic manipulator. Here, the authors presented a method to plan handing-over movements during HRIs under the consideration of a given target position for the passage of an object.…”
Section: Related Workmentioning
confidence: 99%